Mathematical methods for the analysis of color scanning filters - Vora, P L (IEEE transactions on image processing : a publication of the IEEE Signal Processing Society, 1997)
The problem of the sensitivity analysis of color scanning filters is addressed in this paper. The second differential of the mean square DeltaE(ab) error provides a means of calculating the sensitivity of the mean square DeltaE(ab) error to filter fabrication errors. Tolerances on the allowable change in the mean square DeltaE(ab) error are used to define bounds on the filter fabrication errors at all wavelengths and at single wavelengths